Quantum-chemical properties of L-carnitine - Samchenko, Yu.M.; Kernosenko, L.O.; Kryklya, S.O.; Pasmurtseva, N.O.; Poltoratskа, T.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
The distributions of charges and the electrostatic and hydrophobic potentials are analyzed, and the basic reaction centers of a molecule of L-carnitine are revealed. A large dipole moment and the variety of functional groups of the molecule evidence about a possibility of its interaction with polar and nonpolar structures of biomembranes.